Computer simulation of building for lateral loading using css software - Kho, Wendy Choon Yen. (Universiti Malaysia Sarawak, UNIMAS, 2010)
This research is to investigate the behaviour of the three dimensional six storey structure with the different support conditions and combination of vertical and horizontal loads in non linear analysis. In this research, the S-FRAME software is used to analyse the structure and the S-STEEL software is used to check the capacity of the structure with the proposed section member. Both of this software are under Computer Services Consultant (CSC) UK Limited. The supports used for this research are fix support and pin spring support. The purpose of the pin spring support is to simulate the deformation due to earthquake in the vertical direction only. The spring stiffness used in this project is 2000kN/m which gives the deflection of 150mm in z direction. The behaviour of the structure is classified into sway or non sway criteria of the brace frame structure. The criteria of sway and non sway can be determined from the elastic critical load factor for the frame. It is found that the highest elastic critical load factor value of the brace frame structure with fix support is 37500 while the lowest elastic critical load factor value, λcr of brace frame structure with one end of column in pin spring support is 0.30. It is obviously shown that the brace frame structure with fix support is classified as non sway frame while the brace frame structure with one end of column in pin spring support and others is fix support is classified as sway sensitive frame. Some of the section members in the brace frame structure with one end of column in pin spring support failed due to the combination of vertical and horizontal load. User friendly manual procedures are written in Chapter 4 to assist future CSC users.